Міжнародна науково-практична конференція "Графічні технології моделювання об’єктів, процесів та явищ" - Плоский, ВІталій Олексійович; Ботвіновська, Світлана Іванівна; Ісмаілова, Н. П. (КНУБА, 2020)
Представлена інформація про міжнародну науково-практичну конференцію «Графічні технології моделювання об’єктів, процесів та явищ» на базі Військової академії (м. Одеса) The work presents information about the international scientific and practical conference “Graphic technologies of modeling objects, processes and phenomena”. An international conference organized jointly by the Ministry of Education and Science of Ukraine, the Military Ministry of Ukraine, the Ukrainian Association of Applied Geometry, the Military Academy and the Kiev National University of Construction and Architecture was held on the basis of the Academy in Odessa on April 23 - 24, 2020. Scientific and pedagogical workers, associates, postgraduate students, cadets and students of higher educational institutions, volunteers, representatives of enterprises and public organizations were invited to the conference. The aim of the conference is to maximize the use of geometric modeling methods in the field of applied sciences, namely, in the creation and modernization of weapons and military equipment; in mechanical engineering; shipbuilding; aviation industry; design and architecture; Computer technologies, etc. It was noted that geometric and computer modeling techniques and techniques significantly improved the efficiency of creating and using original geometric models. Holding such conferences in the future is an integral part of the maintenance and development of applied science. The participants of the conference noted that the solution of the problems can be achieved only if the efforts of the military community and various civil society institutions, higher education institutions and research institutions that solve the problems of the future development of science in the State are united.
International scientifi and practical conference ''Graphic techologies of modeling of objects, processes and phenomena''
Keywords: geometric modeling; graphic technologies; computer modeling; weapons and military equipment; security and defense technologists; геометричне моделювання; графічні технології; комп’ютерне моделювання; озброєння та військова техніка; технології у секторі безпеки та оборони